THE IMPLEMENTATION OF SIMPLE PRESENT VERB AND VOCABULARY MASTERY TOWARDS STUDENTS' WRITING SKILLS IN PROCEDURE TEXT - Nuhra M Saleh; Muhammad Sulhan (INFERENCE: Journal of English Language Teaching, 2021)
This research is a kind of survey and aims to determine the effects of simple present verb and vocabulary mastery on students' writing skills in procedure text. This research has three variables which are divided into two independent variables and one dependent variable. Test scores do the collection of the data for independent and dependent variables. The gained data were then analyzed by using the multiple regressions method. The results of this research are: 1) There are significant effects of simple present verb and vocabulary mastery towards students' writing skills in procedure text. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 12.541; 2) There is a significant effect of simple present verb towards students' writing skill in procedure text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 2.041; 3) There is a significant effect of vocabulary mastery towards students' writing skills in procedure text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 2.201.Keywords: simple present verb, vocabulary mastery, procedure English text